'Authorized to Depart from the Law': The Curious Case of Viet Nam in Times of COVID-19. (20th September 2021) - Nguyen, Duc Tien
Abstract: The COVID-19 pandemic has posed myriad brain-wracking questions to decision-makers at all levels. Viet Nam managed to curb mortality and morbidity to praiseworthy levels in the past COVID-19 waves, however, has now had its back against the wall amidst the recent exponential infection cases and draining medical resources. For swiftly flattening the curve, the legislature authorized the Government to take bolder steps where needed, even different from the laws. This article argues that while the empowerment comes from the goodwill of the legislature for the purpose of containing the raging outbreak, there remain procedural irregularities. This should garner more attention from the state authority to ensure the rule of law and legality of all state actions during the time of public health emergency.